1993
DOI: 10.2134/agronj1993.00021962008500060015x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Planting Date Effects on Low‐Protein Spring Barley

Abstract: Grain protein of barley (Hordeum vulgare L.) produced for malting often is greater than the industry's acceptable standards of 135 and 130 g kg−1 for six‐rowed and two‐rowed barley, respectively. Environmental conditions such as low rainfall and high temperatures after anthesis often cause increased grain protein. This study was conducted at four dryland environments in North Dakota over 2 yr to compare the effects of N fertilization and planting date on agronomic and malt quality traits of two experimental ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
67
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 8 publications
9
67
1
Order By: Relevance
“…Although Fedak and Mack (1977), Weston et al (1993), and Conry (1995) found that late seeding resulted in higher protein content of the grain, no effect of seeding date on protein content was found in our study (Table 5). This lack of response was unexpected based on the effects of seeding date on percent thins and test weight.…”
Section: Grain Qualitycontrasting
confidence: 79%
See 4 more Smart Citations
“…Although Fedak and Mack (1977), Weston et al (1993), and Conry (1995) found that late seeding resulted in higher protein content of the grain, no effect of seeding date on protein content was found in our study (Table 5). This lack of response was unexpected based on the effects of seeding date on percent thins and test weight.…”
Section: Grain Qualitycontrasting
confidence: 79%
“…Weston et al (1993) also found that late seeding of barley resulted in lower kernel weight. Kernel numbers per spike and spikelet number per spike were not affected by seeding date, and cultivar differences were due to the differences between six-and two-rowed types for these traits (Table 6).…”
Section: Grain Yield and Yield Componentsmentioning
confidence: 89%
See 3 more Smart Citations